The effectiveness of the therapeutic exercise Clinical Pilates in adult patients with multiple sclerosis: a systematic review - Matsouki, Eleni; Kyriakatis, Georgios Marios (International Journal of Clinical Trials, 2024)
Existing literature supports various forms of exercise as appropriate for treating people with multiple sclerosis (MS) with mild or more severe symptoms. In recent years, Pilates is a form of therapeutic exercise used more and more often in rehabilitating people with MS. The purpose of this systematic review is to explore the effectiveness of the clinical Pilates method in adult people with MS. Research was performed in 4 scientific databases (PubMed/MEDLINE, ScienceDirect, PEDro and Scopus) using the following keywords: multiple sclerosis, MS, Pilates and Clinical Pilates. Inclusion criteria were studies randomized controlled, written in English, published in 2012-2022, with adult people with MS and where the intervention should have been only the Pilates method and the results had to be relevant to physiotherapy. The methodological quality of the studies included was assessed by PEDro Scale. From a total of 329 initial records, only 12 studies were included. Results show that Pilates can improve balance, gait, functionality, physical and cognitive capacity, quality of life and body composition in adult people with MS and with mild to moderate disability. Fatigue, anxiety and depression levels did not show clear improvement after the application of the Pilates exercises in comparison with other therapeutic exercises. Pilates is a safe method of exercise for adult people with MS and can improve many symptoms. It is necessary more research to be conducted so that the effectiveness of the Pilates exercises be explored further on different parameters in patients with MS, like fatigue.